Mushrooming Livelihoods: A Socio-economic Analysis of Solan District’s Mushroom Agripreneurs - Sharma, Anju; Chauhan, Ridhi; Sharma, Satish K.; Devi, Nisha; Thakur, Vishal; Verma, Sahil (International Journal of Economic Plants, 2025)
The present study was conducted during September, 2023 to April, 2024 in the Solan district of Himachal Pradesh, India, to assess the socioeconomic status of mushroom growers in the district and identify the key constraints hindering their progress. A survey of 54 randomly selected mushroom farmers was conducted. The findings revealed that most growers were literate, above 40 years of age and engaged in agriculture as their primary occupation. Land utilization varied across farm sizes, influencing productivity and economic returns. Economies of scale played a key role in profitability, with large-scale farmers earning significantly higher incomes. Small-scale growers cultivated an average of 481.48 bags, earning `Rs. 1,24,574, while large-scale farmers handled 3,181.82 bags, securing ` Rs. 9,34,659. The study highlighted the potential of mushroom farming as a sustainable and profitable agricultural practice. While mushroom farming demonstrated strong potential as a sustainable and profitable agricultural venture, farmers faced numerous challenges, including the availability of essential inputs, financial constraints, infrastructure limitations, and quality control. Limited availability of spawned bags was observed as the top challenge (Garrett mean score: 76.58), followed by high capital investment (72.86) and lack of temperature-controlled rooms (68.49). While technical and administrative support, value addition and training were seen as less urgent but still necessary for long-term success. The study suggested that addressing these issues in a holistic manner is crucial for improving the productivity and profitability of mushroom farming, enhancing rural livelihoods and ensuring sustainable agricultural growth in the region.